We need to use words that we'd use in Brazil, right? A Community-Based Content Validation of a Translated Femicide Risk Assessment Instrument. (September 2022) - Manders, Olivia C.; Xavier Hall, Casey D.; Vertamatti, Maria A. F.; Evans, Dabney P.; Campbell, Jacquelyn C.
The Danger Assessment (DA) is a widely-used risk assessment instrument designed to help women understand their risk of femicide. Currently, no validated tool exists in Brazilian Portuguese. The purpose of this study was to conduct a cross-cultural adaptation of the DA for use in the Brazilian context as a precursor to validation and broader testing among women in Brazil. This study describes a community participatory approach for translation and cultural adaptation of the DA from European to Brazilian Portuguese that engages the target population in the process. Using a three-step process, a final version of the DA-Brazil instrument was developed.